Activities of Endochin-Like Quinolones Against in vitro Cultured Besnoitia besnoiti Tachyzoites - Eberhard, Naja; Balmer, Vreni; Müller, Joachim; Müller, Norbert; Winter, Rolf; Pou, Soviti; Nilsen, Aaron; Riscoe, Mike; Francisco, Samuel; Leitao, Alexandre; Doggett, J. Stone; Hemphill, Andrew (Frontiers in Veterinary Science, 2020)
Endochin-like quinolones (ELQs) potently inhibit the proliferation of Plasmodium, Toxoplasma, Neospora and Babesia by targeting the cytochrome b Qo and Qi sites and interfering with oxidative phosphorylation and pyrimidine biosynthesis. The activities of 12 different ELQs were assessed against B. besnoiti tachyzoites grown in human foreskin fibroblasts (HFF) by quantitative real time PCR. The values for 50% proliferation inhibition (IC50) of five ELQs were determined in a three-day growth assay after an initial screen of 12 ELQs at 0.01, 0.1 and 1 µM. The IC50s of ELQ-121, -136 and -316 were 0.49 nM, 2.36 nM and 7.97 nM, respectively. The IC50s of ELQs tested against B. besnoiti were higher than IC50s previously observed for P. falciparum and T. gondii. However, the B. besnoiti cytochrome b sequence and the predicted Qo and Qi ELQ binding sites in the Toxoplasma, Neospora and Besnoitia cytochrome b are virtually identical, suggesting that the differences in ELQ susceptibility are not due to variations in the substrate binding sites. TEM of ELQ-treated parasites primarily demonstrated alterations within the parasite mitochondrion, profound thickening of the nuclear membrane, as well as increased vacuolization within the tachyzoite cytoplasm. Long-term treatment assays of intracellular B. besnoiti with ELQs for up to 20 days followed by the release of drug pressure caused a substantial delay in parasite growth and proliferation while ELQs were present, but parasite proliferation resumed days after ELQs were removed. Interestingly, structural alterations persisted after ELQ removal and parasite proliferation was slowed. These findings provide a basis for further in vivo studies of ELQs as therapeutic options against B. besnoiti infection.